Proposal for a Worldwide Usable Score for the Prediction of Recurrence and Intention-to-Treat Survival after Liver Transplantation in Patients with Hepatocellular Cancer: A West-East Analysis on 1, 903 Patients. (July 2018) - Lai, Quirino; Halazun, Karim J; Iesari, Samuele; Bhangui, Prashant; Finkenstedt, Armin; Mennini, Gianluca; Lin, Chih-Che; Hoppe-Lotichius, Maria; Ikegami, Toru; Xie, Qin-Fen; Zhe, Yang; Zheng, Shu-Sen; et al.
Abstract : EURHECA-LT. Liver transplantation (LT) represents the best strategy for the treatment of hepatocellular cancer (HCC). However, great differences exist among Western and Eastern countries in terms of HCC management, mainly due to the different underlying liver pathology (HBV vs. HCV) and the greater attitude of Asian countries to perform living-donor and salvage LT. Aim of the study was to identify a world-wide usable score able to predict recurrence after LT and poor intention-to-treat survival in both West and East countries. A population of 1, 903 patients enlisted for LT coming from 5 Western (Brussels, Rome Sapienza University, New York Columbia University, Mainz and Innsbruck; n=1, 282) and four Eastern (Guangzhou, Kyushu, New Delhi and Chang Gung Taiwan; n=621) centers was investigated. A total of 1, 774 (93.2%) patients underwent LT, with 236/1, 774 (13.3%) recurrences. At multivariable Cox regression analysis, three independent risk factors for recurrence were identified: high alpha-fetoprotein (AFP) value (defined as slope ≥15 ng/mL/month OR last value ≥1, 000 ng/mL) (hazard ratio=3.32; p-value<0.0001), up-to-seven >7 at last radiological assessment (HR=2.38; p-value<0.0001) and radiological progression disease (HR=1.51; p-value=0.02). Interestingly, neither living donation nor salvage LT or underlying liver diseases were significant risk factors. A score able to stratify the entire population according to the presence of these risk factors was developed: patients without risk factors had an excellent 5-year recurrence rate of 11.2% when compared with patients with a score 1-2, 3-4 and ≥5 (21.5, 33.2 and 60.1%, respectively; p-value<0.0001). Similarly, 5-year ITT-survival was superior in patients without risk factors (76.5%) when compared with patients with score 1-2, 3-4 and ≥5 (66.8, 57.4 and 32.3%, respectively; p-value<0.0001). When separate analyses were done exclusively looking at Western or Eastern patients, similar results were reported, with patients having a score ≥5 presenting 5-year recurrence rates of 64.1 and 59.2% and 5-year ITT-survivals of 24.1 and 41.2%, respectively. This is the first score developed contemporaneously analysing large West-East populations. Interestingly, regional peculiarities were not significant risk factors when the entire population was analysed. The proposed user-friendly score was able to well stratify the population in terms of recurrence and ITT-survival, identifying a small sub-group (n=89; 4.7%) of patients with a value ≥5 presenting unacceptably high risks for death and recurrence.